Níveis de magnésio em solução nutritiva e o desenvolvimento do feijoeiro (Phaseolus vulgaris L. cv Carioca). Avaliação de relações de crescimento e partição de assimilados - Boaro, Carmem Silvia Fernandes; De Moraes, José Antonio Proença Vieira; Rodrigues, João Domingos; Pedras, José Figueiredo; Ono, Elizabeth Orika; Curi, Paulo Roberto [UNESP] (My University, 1996)
The effect of magnesium levels in nutrient solution upon relation between shoot and root, leaf weight ratio and assimilate partitioning of common bean (Phaseolus vulgaris L. cv Carioca) was studied. Bean plants (3 per pot) were grown in 6 1 pots containing Hoagland & Arnon n. 2 solution modified to obtain 2.4, 24.3, 48.6, 72.9 and 97.2 ppm of magnesium. The experimental design was a completely randomized factorial replicated 3 times with 5 levels of magnesium and 5 samplings wich were done forthnightly. Therefore, it may be suggested that the 48.6 ppm of magnesium level proposed by Hoagland & Arnon (1950) is the best choice for the common bean, according to the conditions of this experiment. Magnesium concentrations over 48.6 ppm didn't show significant alterations of the evaluated parameters. Nutrient solution with 2.4 ppm of magnesium content provides higher efficiency to the common bean plants during almost all its cycle, except the final of the reproductive phase. These results suggest that magnesium concentration increased to 48.6 ppm, in the cycle final perhaps could increase the productivity.
Magnesium levels in nutrient solution and common bean (Phaseolus vulgaris L. cv Carioca) development. Evaluation of the growth relations and assimilate partitioning
Keywords: Assimilate partitioning; Magnesium; Phaseolus vulgaris; Relation between shoot and root; Weight leaf ratio